1997
DOI: 10.1111/j.1399-6576.1997.tb04810.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide reduces inspired oxygen fraction but does not compromise circulation and oxygenation during hemodilution in pigs

Abstract: Nitrous oxide did not compromise systemic and myocardial circulation and oxygenation during acute normovolemic hemodilution in pigs. Possible adverse effects from the use of nitrous oxide during hemodilution seem to be related to a reduced F1O2, reducing the safety margin for systemic oxygen delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Thus dislocation boundaries and typical lamellar structure with elongated cells due to the inhomogeneously distributed dislocations appear out. These have also been observed within the shear bands of some other materials such as steels [15][16][17][18][19] and aluminium [20].…”
Section: The Microstructure Within the Shear Bandsmentioning
confidence: 72%
See 1 more Smart Citation
“…Thus dislocation boundaries and typical lamellar structure with elongated cells due to the inhomogeneously distributed dislocations appear out. These have also been observed within the shear bands of some other materials such as steels [15][16][17][18][19] and aluminium [20].…”
Section: The Microstructure Within the Shear Bandsmentioning
confidence: 72%
“…The microstructure evolution during the plastic deformation is the essential issue of this research topic [15][16][17][18][19]. It is rather difficult to observe directly how the microstructure is evolved in the deformation process.…”
Section: The Microstructure Within the Shear Bandsmentioning
confidence: 99%
“…Cho et al [191] considered that the fine equiaxed grains observed in the center region of a shear band in HY-100 steel was caused by dynamic recovery rather than by DRX. It is possible that, in their case, the strain inside the shear band was not sufficient to complete the recrystallization process.…”
Section: G Recrystallizationmentioning
confidence: 99%
“…[22,26] The dominant mechanism driving microstructural changes within ASBs during the shear deformation of metals and alloys is unclear and a number of different mechanisms have been proposed. These include dynamic recovery, [27,28] dynamic recrystallization, [12,21,[29][30][31][32] strain-induced phase transformation, [33,34] amorphization, [20,35] and carbon segregation. [15] The strain-induced phase transformation mechanism has been challenged by researchers who claim that evidence for a phase transformation in ASBs has not been provided [28] and that, even if one did occur, it would be of secondary importance to another mechanism.…”
Section: Introductionmentioning
confidence: 99%